Adjustment of born‐oppenheimer electronic wave functions to simplify close coupling calculations. Issue 11 (23rd January 2013) - Buenker, Robert J.; Liebermann, Heinz‐Peter; Zhang, Yu; Wu, Yong; Yan, Lingling; Liu, Chunhua; Qu, Yizhi; Wang, Jianguo
Abstract Technical problems connected with use of the Born‐Oppenheimer clamped‐nuclei approximation to generate electronic wave functions, potential energy surfaces (PES), and associated properties are discussed. A computational procedure for adjusting the phases of the wave functions, as well as their order when potential crossings occur, is presented which is based on the calculation of overlaps between sets of molecular orbitals and configuration interaction eigenfunctions obtained at neighboring nuclear conformations. This approach has significant advantages for theoretical treatments describing atomic collisions and photo‐dissociation processes by means of ab initio PES, electronic transition moments, and nonadiabatic radial and rotational coupling matrix elements. It ensures that the electronic wave functions are continuous over the entire range of nuclear conformations considered, thereby greatly simplifying the process of obtaining the above quantities from the results of single‐point Born‐Oppenheimer calculations. The overlap results are also used to define a diabatic transformation of the wave functions obtained for conical intersections that greatly simplifies the computation of off‐diagonal matrix elements by eliminating the need for complex phase factors. © 2013 Wiley Periodicals, Inc.